2018
DOI: 10.1093/jrr/rry066
|View full text |Cite
|
Sign up to set email alerts
|

Impact of prophylactic cranial irradiation on pattern of brain metastases as a first recurrence site for limited-disease small-cell lung cancer

Abstract: This study sought to evaluate the impact of prophylactic cranial irradiation (PCI) on the pattern of brain recurrence after radical treatment in patients with limited-disease small-cell lung cancer (LD-SCLC). Patients treated with radiotherapy and chemotherapy between January 2006 and December 2014 at a single institution were retrospectively examined. Radiotherapy was performed using accelerated hyperfractionated radiotherapy (twice daily, 45 Gy in 30 fractions) or conventional fractionated radiotherapy (once… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(22 citation statements)
references
References 23 publications
0
22
0
Order By: Relevance
“…In addition to symptomatic BM, we found that the pre-PCI BM (BM immediately before PCI) was investigated in one study (36) and the first isolated BM event, rather than overall BM during the whole disease course, was analyzed in five studies (37)(38)(39)(40)(41). Both the first isolated BM and overall BM were reported in eight papers (28)(29)(30)(42)(43)(44)(45)(46) and showed that the first isolated BM incidence was lower than the overall BM incidence (Table 1).…”
Section: Study Selection and Quality Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to symptomatic BM, we found that the pre-PCI BM (BM immediately before PCI) was investigated in one study (36) and the first isolated BM event, rather than overall BM during the whole disease course, was analyzed in five studies (37)(38)(39)(40)(41). Both the first isolated BM and overall BM were reported in eight papers (28)(29)(30)(42)(43)(44)(45)(46) and showed that the first isolated BM incidence was lower than the overall BM incidence (Table 1).…”
Section: Study Selection and Quality Assessmentmentioning
confidence: 99%
“…We also found that the definition of time to BM events varied among studies, which indicates that heterogeneity also exists between RCTs: from the date of initial diagnosis (n = 19) (45, 49, 51, 53, 55, 58-62, 64, 66, 71, 72, 74-76, 78, 81); from the date of randomization (n = 16) (5, 9, 25, 26, 28-32, 34, 35, 41, 46, 68, 79, 80); from the date of treatment initiation (n = 6) (37,42,47,57,69,77); from the end of chemoradiotherapy (CRT) (n = 5) (44,47,67,70,78); from the date of PCI (n = 4) (27,48,54,65); from the date of chemotherapy initiation (n = 3) (33,38,39); from the date of TRT initiation (n = 2) (43,56); from the date of surgery (n = 1) (50); five studies had no information (36,40,52,63,73), two studies applied two definitions (47,78).…”
Section: Study Selection and Quality Assessmentmentioning
confidence: 99%
“…The differences between the PCI and non-PCI groups in terms of numbers and time to appearance of BM as a first recurrent site affected OS. These results were similar in all groups (pre-CRT MRI group/pre-PCI MRI group/pre-CRT and pre-PCI MRI group) [ 11 ]. Our study is similar in that PCI contributes to extending the time to appearance of BM.…”
Section: Discussionmentioning
confidence: 53%
“…PCI had a significant positive impact on patient prognosis after radical treatment for LS-SCLC in the report from Nakamura et al. [ 11 ]. The differences between the PCI and non-PCI groups in terms of numbers and time to appearance of BM as a first recurrent site affected OS.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to the EORTC trial, 59% of symptomatic BM patients in the non-PCI cohort received cranial radiotherapy compared with 8.3% in the PCI cohort (10). In addition, Nakamura et al reported that among BM patients, those who underwent PCI had a better outcome (3-year OS, 17% vs. 0%, P = 0.005) and fewer BM incidents (>5 BM, 12% vs. 68%, P < 0.001), which suggests the possibility of performing salvage stereotactic radiosurgery (SRS) (27).The results of the retrospective studies were consistent with these findings. Chen et al (28) found a significant increase in BM-free survival in the PCI group (P = 0.002), with a 1-year BM incidence of 17% in the PCI and 56% in the non-PCI groups.…”
Section: Meta-analysesmentioning
confidence: 99%